Approach–Avoidance Motivation and Information Processing: A Cross-Cultural Analysis - Hamamura, Takeshi; Meijer, Z.; Heine, S.; Kamaya, K.; Hori, I. (Sage Publications, Inc., 2009)
Much recent research suggests that North Americans more frequently experience approach motivations and East Asians more frequently experience avoidance motivations. The current research explores some cognitive implications of this cultural difference. North Americans should be more attentive to approach-oriented information, whereas East Asians should be more attentive to avoidance-oriented information. Three studies confirmed this hypothesis. When asked to recall information framedin either approach or avoidance terms, a predicted interaction between culture and information frame was observed (Study 1 and 2). Moreover, analyses of consumer book reviews found that among reviews that were rated as helpful, approach-focused content was more prevalent in American reviews compared to Japanese reviews, in which avoidance-focused content was more prevalent (Study 3). Findings from the current research add to the growing literature of cross-cultural researchon approach–avoidance motivations.